2005
DOI: 10.1111/j.1469-0691.2005.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic assessment of the in-vivo efficacy of imipenem alone or in combination with amikacin for the treatment of experimental multiresistant Acinetobacter baumannii pneumonia

Abstract: A guinea-pig pneumonia model involving imipenem-susceptible and imipenem-resistant strains of Acinetobacter baumannii was developed to assess the in-vitro and in-vivo activities of imipenem, alone or in combination with amikacin, and the pharmacokinetic and pharmacodynamic parameters. Serum levels were measured by bioassay (imipenem) or immunoassay (amikacin), followed by calculation of pharmacokinetic and pharmacodynamic parameters (Cmax, AUC, t1/2, Cmax/MIC, AUC/MIC, and Deltat/MIC). In-vivo efficacy was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…Likewise in an experimental pneumonia model in guinea pigs, Bernabeu-Wittel et al [108] showed that the combination of amikacin with imipenem was not as effective as monotherapy with imipenem in reducing the bacterial concentration in the lungs, probably because of an in vivo chemical drug--drug interaction, resulting in decreased pharmacokinetics/pharmacodynamics parameters for both antibacterial agents. In summary, neither study supports the addition of amikacin to imipenem in the treatment of A. baumannii pneumonia.…”
Section: Combination Of Antibacterial Agentsmentioning
confidence: 98%
“…Likewise in an experimental pneumonia model in guinea pigs, Bernabeu-Wittel et al [108] showed that the combination of amikacin with imipenem was not as effective as monotherapy with imipenem in reducing the bacterial concentration in the lungs, probably because of an in vivo chemical drug--drug interaction, resulting in decreased pharmacokinetics/pharmacodynamics parameters for both antibacterial agents. In summary, neither study supports the addition of amikacin to imipenem in the treatment of A. baumannii pneumonia.…”
Section: Combination Of Antibacterial Agentsmentioning
confidence: 98%
“…In contrast, bacteria are often cleared in murine pneumonia models. Therefore, in the majority of Acinetobacter murine pneumonia models reported on to date, the animals received porcine mucin with the bacterial challenge (4,25,26,34,36) or were rendered neutropenic (20, 21), permutations FIG. 9.…”
Section: Discussionmentioning
confidence: 99%
“…However, antibiograms performed on these strains showed a rough correlation between virulence and degree of antibiotic resistance, a relationship that has not previously been investigated. The tendency for A. baumannii strains to exhibit a high level of antibiotic resistance is well established in the literature (1,2,6,7,18,20,22,27,28,33,39,49,59). Resistance is due both to chromosomally encoded resistance genes and to ones found on plasmids and transposons (12).…”
Section: Characterization Of Systemic a Baumannii Infection Five CLmentioning
confidence: 99%